2011
DOI: 10.1007/s12199-011-0255-5
|View full text |Cite
|
Sign up to set email alerts
|

Eleusine indica L. possesses antioxidant activity and precludes carbon tetrachloride (CCl4)-mediated oxidative hepatic damage in rats

Abstract: The results of our study indicate that the hepatoprotective effects of E. indica might be ascribable to its antioxidant and free radical scavenging property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…On the other hand solubility and stereochemical structure of inulin exposes the OH groups for interaction with fluoride ions. Differences in fluoride removal efficiencies of the sisal fibre, maize leaf, goosegrass, banana false stem and untreated sisal fibres (USF) may be attributed to the small and different proportions of steriochemically open and relatively soluble active compounds such as tannins and glycosides relative to cellulose in maize leaf, goosegrass, banana false stem and inulin relative to cellulose in untreated sisal fibres [33,34]. The presence of these compounds in the biomass is attributable to preparation procedures employed which did not involve removal of the water soluble impurities from the biomass.…”
Section: The Effect Of Solubility and Stereochemistry Of The Active Cmentioning
confidence: 99%
“…On the other hand solubility and stereochemical structure of inulin exposes the OH groups for interaction with fluoride ions. Differences in fluoride removal efficiencies of the sisal fibre, maize leaf, goosegrass, banana false stem and untreated sisal fibres (USF) may be attributed to the small and different proportions of steriochemically open and relatively soluble active compounds such as tannins and glycosides relative to cellulose in maize leaf, goosegrass, banana false stem and inulin relative to cellulose in untreated sisal fibres [33,34]. The presence of these compounds in the biomass is attributable to preparation procedures employed which did not involve removal of the water soluble impurities from the biomass.…”
Section: The Effect Of Solubility and Stereochemistry Of The Active Cmentioning
confidence: 99%
“…The decoctions of the boiled whole plant are consumed for antihelminthic and febrifuge treatment [12]. The seed of E. indica is sometimes used as famine food and in the treatment for liver complaints [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Several pharmacological properties on E. indica have been reported including hepatoprotective effect [13], antiplasmodial and antidiabetic [14], antioxidant and antimicrobial activity [8], anti-inflammatory [15], and cytotoxic effect towards several cancer cell lines [8, 16]. To date, only one study reported the isolation of secondary metabolites from E. indica where hexadecanoic acid and [[(2-aminoethoxy) hydroxyphosphinyloxy]methyl]-1,2–ethanediylester were isolated [17].…”
Section: Introductionmentioning
confidence: 99%
“…Positive results in all the antioxidant activity assays used in this study indicate that the various compounds in the crude extracts could act as free radicals’ scavenger viz., DPPH, ABTS, SOR or possess the reducing power potential of Fe 3+ , Cu 2+ and Mo (IV) complex. Devi and Kottai [ 42 ], Iqbal and Gnanaraj [ 51 ] and Rekha and Shivanna [ 52 ] also reported antioxidant activity in S. spontaneum, E. indica and D. aegyptium. Intake of such antioxidants protect the body from damage caused by harmful molecules such as free radicals, ultimately lowering the risk of infections and some forms of cancer and so, improves the health.…”
Section: Discussionmentioning
confidence: 99%